Genome-Wide Identification and Classification of Soybean C2H2 Zinc Finger Proteins and Their Expression Analysis in Legume-Rhizobium Symbiosis - Yuan, Songli; Li, Xiangyong; Li, Rong; Wang, Lei; Zhang, Chanjuan; Chen, Limiao; Hao, Qingnan; Zhang, Xiaojuan; Chen, Haifeng; Shan, Zhihui; Yang, Zhonglu; Chen, Shuilian; et al. (Frontiers in microbiology, 2018)
Root nodule symbiosis (RNS) is one of the most productive and economical systems for nitrogen fixation, and previous studies have shown that several nodule-specific C2H2-zinc finger proteins (ZFPs) play important roles in symbiosis establishment and nodule function. However, C2H2-ZFPs are the most widespread ZFPs in eukaryotes, and a great variation of structure and function exist among the family members. It remains largely unclear whether or not special types of C2H2-ZF genes participate in symbiosis, especially in soybean. In the present study, we performed a genome-wide survey of soybean C2H2-ZF genes, and 321 soybean C2H2-ZF genes were identified and classified into 11 clearly distinguishable subsets (Gm-t1-SF, Gm-t2-SF, Gm-1i-Q-SF, Gm-1i-M-SF, Gm-1i-Z-SF, Gm-1i-D-SF, Gm-2i-Q-SF, Gm-2i-M-SF, Gm-2i-Mix-SF, Gm-3i-SF, and Gm-4i-SF) based on the arrangements, numbers, and types of C2H2-ZF domains. Phylogenetic and gene ontology analyses were carried out to assess the conserved sequence and GO function among these subsets, and the results showed that the classification of soybean C2H2-ZFPs was reasonable. The expression profile of soybean C2H2-ZFPs in multiple tissues showed that nearly half of soybean C2H2-ZFPs within different subsets had expressions in nodules, including a clustering branch consisting of 11 Gm-1i-Q-SF genes specifically expressed in symbiotic-relative tissues. RNA-Seq was used to identify symbiosis-related soybean C2H2-ZFPs, and the expression pattern of the soybean C2H2-ZFPs in roots and nodules at different development stages showed that soybean C2H2-ZFPs mainly played roles in nodule development or nodule function rather than nodulation signal transduction, and nearly half of these genes had high expressions and/or different expression patterns during soybean nodule development, especially for the six clustering branches of genes consisting of different subsets of C2H2-ZFPs. Furthermore, the selected symbiosis-related soybean C2H2-ZFPs might function in legume-rhizobium symbiosis through regulating or interacting with other key proteins. Taken together, our findings provided useful information for the study on classification and conservative function of C2H2-ZFPs, and offered solid evidence for investigation of rhizobium symbiosis-related C2H2-ZFPs in soybean or other legumes.